Whole-genome resequencing reveals genetic diversity, differentiation, and selection signatures of yak breeds/populations in Qinghai, China - Li, Guangzhen; Luo, Jing; Wang, Fuwen; Xu, Donghui; Ahmed, Zulfiqar; Chen, Shengmei; Li, Ruizhe; Ma, Zhijie (Frontiers in Genetics, 2023)
The Qinghai Province of China is located in the northeast region of the Qinghai–Tibetan Plateau (QTP) and carries abundant yak genetic resources. Previous investigations of archaeological records, mitochondrial DNA, and Y chromosomal markers have suggested that Qinghai was the major center of yak domestication. In the present study, we examined the genomic diversity, differentiation, and selection signatures of 113 Qinghai yak, including 42 newly sequenced Qinghai yak and 71 publicly available individuals, from nine yak breeds/populations (wild, Datong, Huanhu, Xueduo, Yushu, Qilian, Geermu, Tongde, and Huzhu white) using high-depth whole-genome resequencing data. We observed that most of Qinghai yak breeds/populations have abundant genomic diversity based on four genomic parameters (nucleotide diversity, inbreeding coefficients, linkage disequilibrium decay, and runs of homozygosity). Population genetic structure analysis showed that Qinghai yak have two lineages with two ancestral origins and that nine yak breeds/populations are clustered into three distinct groups of wild yak, Geermu yak, and seven other domestic yak breeds/populations. FST values showed moderate genetic differentiation between wild yak, Geermu yak, and the other Qinghai yak breeds/populations. Positive selection signals were detected in candidate genes associated with disease resistance (CDK2AP2, PLEC, and CYB5B), heat stress (NFAT5, HSF1, and SLC25A48), pigmentation (MCAM, RNF26, and BOP1), vision (C1QTNF5, MFRP, and TAX1BP3), milk quality (OPLAH and GRINA), neurodevelopment (SUSD4, INSYN1, and PPP1CA), and meat quality (ZRANB1), using the integrated PI, composite likelihood ratio (CLR), and FST methods. These findings offer new insights into the genetic mechanisms underlying target traits in yak and provide important information for understanding the genomic characteristics of yak breeds/populations in Qinghai.